Language function improvement and cortical activity alteration using scalp acupuncture coupled with speech-language training in post-stroke aphasia: A randomised controlled study - Bingbing Lin; Jinglei Ni; Xiao Xiong; Lanlan Zhang; Jian Song; Mengxue Wang; Linsong Chai; Yunshi Huang; Jia Huang (Complementary Therapies in Medicine)
Background: Scalp acupuncture is commonly used as a complementary treatment to improve language function in patients with post-stroke aphasia. Our objectives were to evaluate the impact of scalp acupuncture on the cerebral cortex of post-stroke aphasia patients. Methods: This assessor-blinded, parallel-arm design, single-center, randomized clinical trial recruited 64 patients with post-stroke aphasia. They were randomly assigned to either the acupuncture group (n = 32) or the control group (n = 32). The primary outcome measure was the Western Aphasia Battery (WAB) score, while the secondary outcome was the oxygenated haemoglobin (OxyHb) index, which represents cortical activity as measured by functional near-infrared spectroscopy (fNIRS). All assessments were performed at baseline and post-intervention. Results: The acupuncture group showed significant improvements in WAB subscales (Spontaneous Speech, Comprehension, Repetition, Naming, and AQ) with all changes statistically significant (P < 0.001). The acupuncture group also showed higher OxyHb indices in the left frontopolar area, left fusiform gyrus, and left pars opercularis (P < 0.05). Additionally, OxyHb D-values were significantly greater in the left frontopolar area and right superior temporal gyrus (P < 0.05) compared to the control group. Among non-global aphasia patients, acupuncture improved comprehension and naming tasks, with lower OxyHb in the right visual association cortex and angular gyrus (P < 0.05). In global aphasia patients, improvements were seen in the AQ and Repetition scores, with higher OxyHb in the right inferior prefrontal gyrus (P < 0.05). Conclusion: Adjuvant scalp acupuncture enhances the effectiveness of speech-language therapy in treating repetition and naming impairments in patients with post-stroke aphasia. Additionally, it may modulate cortical activation in the left frontopolar area, left fusiform gyrus, left pars opercularis, and right superior temporal gyrus, and induces different cortical alteration patterns in global and non-global aphasia.